The association of chronic, enhanced immunosuppression with outcomes of diabetic foot infections - Ilker Uçkay; Madlaina Schöni; Martin C. Berli; Fabian Niggli; Emil Noschajew; Benjamin A. Lipsky; Felix W. A. Waibel (Endocrinology, Diabetes & Metabolism, 2022)
Abstract We investigated if a chronic, enhanced immunosuppressed condition, beyond the immunodeficiency related to diabetes, is associated with clinical failures after combined surgical and medical treatment for diabetic foot infection (DFI). This is a case‐control cohort study in a tertiary centre for diabetic foot problems, using case‐mix adjustments with multivariate Cox regression models. Among 1013 DFI episodes in 586 patients (median age 67 years; 882 with osteomyelitis), we identified a chronic, enhanced immune‐suppression condition in 388 (38%) cases: dialysis (85), solid organ transplantation (25), immune‐suppressive medication (70), cirrhosis (9), cancer chemotherapy (15) and alcohol abuse (243). Overall, 255 treatment episodes failed (25%). By multivariate analysis, the presence (as compared with absence) of chronic, enhanced immune‐suppression was associated with a higher rate of clinical failures in DFI cases (hazard ratio 1.5, 95% confidence interval 1.1–2.0). We conclude that a chronic, enhanced immune‐suppressed state might be an independent risk factor for treatment failure in DFI. Validation of this hypothesis could be useful information for both affected patients and their treating clinicians.